ANALISIS KEMAMPUAN MENULISKATA TULISAN ARAB MELAYU SISWA KELAS VI SD NEGERI 164 PEKANBARU - Anggi Gusnita; Tasya Almajirah; Wilda Milissa Putri; Hasnah Faizah (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2023)
The problem in this study is how the ability to write Malay Arabic words in class VI SD Negeri 164 Pekanbaru. Based on these problems, the purpose of this study was to determine the ability to write Malay Arabic words for class VI SD Negeri 164 Pekanbaru. The data in this study were objects in the form of class VI students at SD Negeri 164 Pekanbaru. The data collection method in this study was carried out in the field by giving a skills test to analyze word writing errors in Malay Arabic written discourse, then the results were collected. The research data is in the form of ability test results to analyze writing errors in Malay Arabic written words obtained from the research sample. The research sample was used as a data source in this study, namely all fourth grade students at SD Negeri 164 Pekanbaru, with a total of 38 students. Data processing techniques for ability tests are by collecting, assessing, presenting and concluding existing data. Data collection in this study was taken using an assessment instrument. The conclusion obtained in this study is that the ability to write words in Arabic Malay of 6th grade students at SD Negeri 164 Pekanbaru is in the "low" category with a percentage of 5.53%. The application of this learning is expected that students can write words with letters that are arranged into an Arabic-Malay word. However, the categories and percentages of the results of the questionnaires that were distributed indicated that the students were not fully able to write words in Arabic-Malay. There are some students who have mastered letters and are adept at composing Arabic-Malay letters fluently, even though they are not very neat. From the research that has been done, there are also some students who are still not fluent in stringing letters due to the lack of practice in writing Arabic-Malay.